Compendio de las enfermedades de las plantas / Bernardo Latorre Guzman (EDICIONES UC, 2018)
Compendium of Plant Diseases is a synoptic description of the main pathologies that affect plants cultivated in Mediterranean and subtropical areas with an emphasis on the most economically important diseases for Latin America. This work has its origin in the book Diseases of Cultivated Plants, perhaps the largest reference in the area and whose last and sixth edition was published in 2004. Since then, plant pathology has undergone accelerated progress and the latest research is incorporated here and practices in etiology, epidemiology and control of diseases, in the context of a modern, sustainable and environmentally friendly agriculture. Consequently, this book aims to become an indispensable reference guide that guides professionals, students and agricultural producers for better decision-making on phytopathological aspects of crops.